Studying the foundations and documentations of personal status systems in Islamic countries - Qiasi Siamak (Kom: Časopis za Religijske Nauke)
Personal status is a set of traits and status in a person distinguishing him from others and defining his legal position in society. In Islamic countries, there is a close relationship between the foundations of personal status and religion. In such a way that until the end of the 19th century, only the laws of Islam ruled over the Islamic countries, and since then, there have been gradual changes in the laws of the Islamic countries. These changes have a special trajectory that has continued until now. The question of the current research is the evolution of personal status systems in Islamic countries which foundations and documents have been based on. It seems that the personal status is based on certain epistemological foundations and documents. Accordingly, there are different systems in the field of personal status in different countries. Examining the change and evolution of jurisprudential and legal ideas in the issue of personal status, along with observing the documents and foundations of jurisprudence and law scholars in this issue, helps to approximate the approaches, and as a result, the regulations can be brought closer together in the feedback that is obtained in the legislation. This research, by examining the foundations and documentations of personal status systems of Islamic countries, in a descriptive-analytical method, shows that these systems are formed based on specific epistemological and methodological foundations and documentations, and the personal statuses of Islamic countries have significant commonalities.